A review on the synthesis and properties of hydroxyapatite for biomedical applications. Issue 2 (24th January 2022) - DileepKumar, V. G.; Sridhar, Mysore Santosh; Aramwit, Pornanong; Krut'ko, Valentina K.; Musskaya, Olga N.; Glazov, Ilya E.; Reddy, Narendra
Abstract: Hydroxyapatite (HA or HAp) is one of the most preferred biomaterials, specifically for bone tissue engineering. HAp is available naturally and is also chemically synthesized. The properties, shape, size and crystalline structure and applications of HAp vary widely depending on the source and extraction methods used. In addition to conventional chemical approaches such as precipitation or sol-gel techniques, newer methods such as microwave synthesis and atomic-layer deposition provide an opportunity to generate HAp with desirable structure and properties. Various methods used for the synthesis of HAp have their own pros and cons. Hence, it is essential to understand the role of specific methods and conditions on the properties and structure of HAps in order to obtain HAp with properties suitable for specific applications. In addition to pure HAp, substantial efforts have been made to dope HAp with various minerals or bioentities to enhance their suitability for medical, environmental remediation and other approaches. In this review, we provide an overview of the various chemical methods used to produce HAp, properties of the HAp produced and its potential applications. Particular focus of this paper is on the co-relation between properties and processes used to synthesis HAp. This review will enable readers to quickly understand the importance of synthesis methods and conditions on the properties of HAp and choose appropriate means to generate HAp with desired properties for specific applications. Graphical Abstract: UF0001